Analysis of Community Behavior Factors in Waste Disposal at Margamukti Village, North Sumedang District in 2023 - Walimah, Ely; Aryanti, Santika; Effendi, Achyar (PHSAJ - Public Health Sebelas April Journal, 2024)
The problem of waste in various countries in the world is still an unresolved polemic, including in Indonesia. Waste can cause various problems both in terms of health and the environment. Moreover, the behavior of people or individuals who disposed waste on the side of the road, in addition to having an impact on health and polluting the environment, also causes a bad smell and spoils the view of motorists. This study aims to explore people's behavior of throwing garbage to the side of the Sukajadi Dam Road. This research uses descriptive research with a qualitative approach. Data collection techniques are interviews, observation and documentation with five research subjects. The results of the study were; 1) the community already has knowledge about the impact of the environment; 2) the community's concern for the environment is quite good; 3) as for the actions taken by the community and the Village government in minimizing pollution from waste by working together to hold cleaning activity day on Friday; 4) in Margamukti Village, facilities such as TPS have not been provided, due to space permits, funding, as well as the effects of holding temporary dump; 5) lack of public awareness and not yet provided cleaning facilities, so that the habit of littering continues; 6) the weak role of the village government in implementing regulations and providing socialization to the community related to environmental cleanliness.